Dissident philosophers voices against the political current of the academy - Hillman, T. Allan, 1978-; Borland, Tully, 1974- (Rowman & Littlefield, 2022)
"This collection gives voice to philosophers who are at odds with the predominant leftist political trends of academic philosophy. Chapters detail personal experiences and reflections on the intellectual viability of a non-left-leaning political philosophy, arguing that conservative thought has an important place in contemporary academia"--